Quantitative weighted estimates for rough homogeneous singular integrals - Hytönen, Tuomas P.; Roncal, Luz; Tapiola, Olli (Israel journal of mathematics, 2017)
We consider homogeneous singular kernels, whose angular part is bounded, but need not have any continuity. For the norm of the corresponding singular integral operators on the weighted space L 2 ( w ), we obtain a bound that is quadratic in A 2 constant [ w ] A 2 . We do not know if this is sharp, but it is the best known quantitative result for this class of operators. The proof relies on a classical decomposition of these operators into smooth pieces, for which we use a quantitative elaboration of Lacey's dyadic decomposition of Dini-continuous operators: the dependence of constants on the Dini norm of the kernels is crucial to control the summability of the series expansion of the rough operator. We conclude with applications and conjectures related to weighted bounds for powers of the Beurling transform.